A critical analysis of the universalization of human rights in the face of systemic relativism: a reality beyond hermeneutics - Iribure Júnior, Hamilton da Cunha; Xavier, Gustavo Silva (REVISTA QUAESTIO IURIS, 2021)
This article analyzes human rights based on the observation that their genesis occurs in a specific historical and cultural context, and that they express the worldview of their birthplace - the Western world - with its ideologies, customs, values and beliefs. Ramon Panikkar and Boaventura de Sousa Santos, who refer to this analysis, advocate the thesis that the universality of human rights can only be achieved through a diatopical hermeneutics, which contemplates the multiplicity of cultures existing in the whole world, because a hermeneutics that insists on the predominance of the values of Western cultures will not find legitimacy before several other cultures, which will feel excluded. The problem that pervades this research is rooted in the universalism/relativism binomial of human rights. The research is justified due to the disparate ways of understanding and applying Human Rights in the various regions of the world, and the importance of overcoming the universalism/relativism antithesis with regard to Human Rights. The diatopical hermeneutics and emancipatory multiculturalism, both making use of intercultural dialogue, are configured as a path for the construction of dialogue on the universalization of rights and the reconstruction and reconceptualization of human rights at a global level, respecting the local particularities of each culture. To this end, the analytical-deductive investigative methodology is employed.